Computational analysis and expression profiling of potassium transport-related gene families in mango (Mangifera indica) indicate their role in stress response and fruit development - Tan, Lin; Waqas, Muhammad; Rehman, Abdul; Rashid, Muhammad Abdul Rehman; Fiaz, Sajid; Manzoor, Hamid; Azeem, Farrukh (Frontiers in Plant Science, 2023)
Potassium (K+) is one of the most abundant ions in plant cell. It is important for various biological functions related to plant growth, development, and flowering/fruiting. Mango (Mangifera indica) fruit is known for its taste, health benefits, and drought tolerance. Potassium significantly contributes to fruit yield, quality, and drought tolerance in plants. However, molecular mechanisms comprising potassium transport in mango are least known. In present study, 37 members of potassium transport-related genes (PTGs) were identified in mango, which include 22 K+ transporters (16 HAKs, 1 HKT, and 6 KEAs) and 15 K+ channels (6 TPKs and 8 Shakers). All PTGs were predicted to be expressed at plasma membrane and possess characteristic motifs and domains. Phylogenetic analysis identified a strong kinship of PTGs among Oryza sativa, Arabidopsis thaliana, Cicer arietinum, Malus domestica, and M. indica. . The promoter analysis identified 60 types of cis-elements related to various biological processes. RNA-seq-based expression profiling identified that MiTPK1.2, MiHAK1, MiHAK2.1, HAK6.1, and MiAKT1.1 were most upregulated in roots, and MiKEA2, MiAKT2, and MiAKT1 were upregulated in leaves. Moreover, MiAKT6, MiHAK1.1, MiKAT2, MiKAT2.1, MiHKT1, MiTPK1.1, MiHAK7, and MiHAK12 were highly expressed during the five growth stages of mango fruit. Current study is the first comprehensive report on K+ transport system in tropical fruits. Therefore, it will provide the foundation knowledge for the functional characterization of K+ genes in mango and related plants.